Pengaruh Kecemasan Berolahraga terhadap Motivasi Berprestasi Atlet Bulutangkis Remaja di Klub J Jakarta - Evelin Intan Clarasasti; Devi Jatmika (Humanitas (Jurnal Psikologi), 2017)
Badminton is the largest contributor to Indonesia's sports achievements in the international arena. High achievement motivation necessary for athletes to be able to maximize the achievement. However, there are problems of anxiety experienced by adolescent athletes PB Jaya Raya Jakarta. The purpose of this study was to assess the effect of anxiety to the achievement motivation in adolescent atheletes in PB Jaya Raya Jakarta. This study uses quantitative methods with the type of causal comparative research. The study involved 158 adolescents who have been through the assessment stage of self-criticism with an age range of 15-21 years. Characteristics of the subjects in this study, namely young men and women athletes, aged 12-18 years, and active to practice. Data can be obtained using the research instrument which are then analyzed using SPSS 17. Researcher looked at the effect of self-concept on the purchase intention by using simple linear regression techniques. The analysis results, showing that the anxiety have a significant influence on the achivement motivation. The effect from self-concept by 23,3%, so there are 76.7% other factors that influence. Therefore, it is advisable to adolescent badminton athletes in order to better control the anxiety in the match and more motivated to achievement.